People, process and system design of smart office solution - Tham, Cheong Sheng (2022)
In a smart building, physical and computational elements such as people, processes and systems are integrated to create an environment that is safe, energy-efficient, comfortable for its occupants. Due to 4th Industrial Revolution (IR 4.0), many organizations are taking initiatives to practice and develop smarter solutions to reduce operation cost using building automations and innovations that also brings values to human productivity. The issue of maintenance and management of office building needed to be study to establish the good proposal of smart building solutions. This research was first determined the people and their responsibilities involving in the building operation of an office building through first phase of purposive sampling interviews. Multiple second phase of process as-is workshop interviews were carried out with building management team and related departments to identify the challenges and issues on maintenance and management issue in office building and their aspiration of modern energy-efficient building. Accordingly, there were 30 respondents from the organization participated in these workshop interviews, 23 type of building operation related processes and 4 main categories of related systems were studied in this research. The office building consisting of a mix of digitalised and manual processes, due to the lack of integration between the different systems employed, it was further complicated by the lack of coordination between the separate departments who work with separate system. These data were then analysed by 8 building experts to introduce a set of proposed smart building solutions for improving the building operation management, promote energy-saving in building system and enhance productivity of occupants. Moreover, the benefits of this research are that the proposed building management solutions can be applied to a variety of smart buildings by considering the building’s physical models, environmental conditions, comfort specifications, occupants’ preferences and safety in the design.